UPAYA GURU PAI DALAM MENGINTERNALISASIKAN NILAI-NILAI KEDISIPLINAN MELALUI SHALAT DHUHA BERJAMAAH SISWA MTS N 1 WONOSOBO - Revina Hidayatul Aziza (JOURNAL SAINS STUDENT RESEARCH, 2025)
Because of the values of punctuality, togetherness, and obedience to religious rules, congregational Dhuha prayer is considered one of the best ways to build a disciplined character. This thesis aims to: 1) Understand how the implementation of congregational Dhuha prayer by students of MTs N 1 Wonosobo; 2) Understand the efforts of Islamic Religious Education teachers in internalizing the values of discipline through the congregational Dhuha prayer of students at MTs N 1 Wonosobo; 3) Identify the supporting and inhibiting factors in the efforts of Islamic Religious Education teachers to internalize the values of discipline through the congregational Dhuha prayer of students at MTs N 1 Wonosobo. This thesis uses a qualitative research approach, where the type of research is descriptive. The data collection techniques used are observation, interviews, and documentation methods. Then, the data sources were obtained through several informants, namely the principal, PAI teachers, and 30 eighth-grade academic students. The data analysis techniques used were data reduction, data presentation, and conclusion or verification. The research results show that 1) the implementation of congregational Dhuha prayers at MTs N 1 Wonosobo is carried out regularly with a rotating schedule among classes, aimed at addressing the limitations of facilities and the large number of students. This activity not only serves as an act of worship but also as a medium for teaching discipline and character building in students in accordance with the madrasah's vision. 2) The efforts of PAI teachers in internalizing the values of discipline through congregational dhuha prayers are systematic and structured, involving the active role of teachers as role models and guides, and supported by good communication with parents and school staff. 3) The supporting factors for the success of this program include adequate worship facilities, regular schedule arrangements, and a religious school environment. However, there are hindering factors such as low student motivation, minimal family support, limited facilities, and a lack of student understanding regarding the importance of congregational dhuha prayers. Therefore, further efforts are needed to overcome these obstacles so that the value of discipline can be optimally instilled in the students.